THE SINGLE PARENT FAMILY FROM A SOCIAL WORK PERSPECTIVE (PANGEEA, 2025)
The topic of single parenthood is a sensitive one, and one that has been increasingly debated lately. From two-parent families who choose to go their separate ways, families in which there is a death, families in which one parent goes abroad to work and does not return and the children stay with either the other parent or with grandparents or other relatives, to children who are born due to a lack of protection for teenagers and one of the future parents does not take responsibility for raising a child, to girls who are raped and become pregnant and choose to give birth to their child, or minors who become pregnant and eventually stay with the children. In modern society, the disintegration of the extended family takes place at a time when land is declining in economic value and the most important asset becomes money, with the development of a highly technological industry. The shrinking of the family size has caused important changes in the lifestyle of the family group as the family has lost its economic, political and religious relevance. The control of the elderly over the young is becoming less oppressive and marriage no longer concerns the interests of the family as a whole, but asserts the independence of the individual to choose his or her marital partner and the time of marriage
Keywords: single parent family; difficulties specific; single mothers; single fathers